Environmentally friendly polymeric plasticizer for poly (vinyl chloride) / Nur Zahidah Rozaki - Nur Zahidah , Rozaki (2018)
Polymeric plasticizers for poly(vinyl chloride), PVC were synthesized using palm oil as the main raw material. A total of four plasticizers with different average molecular weight were prepared. Chemical structure of the plasticizer was analysed using FTIR (Fourier-transform infrared) and 1H-NMR (proton-nuclear magnetic resonance), while the molecular weights were obtained using the GPC (gel permeation chromatography). Plasticization of PVC was carried out using solvent casting technique with tetrahydrofuran, THF as the mutual solvent. Several tests were conducted to investigate the effect of different molecular weights on the efficiency of the palm oil-based compounds as plasticizers for PVC. The performance of the palm oil-based plasticizer was also compared with two commonly used plasticizers for PVC, diethylhexyl phthalate (DEHP) and acetyl triethyl citrate (ATEC). Some of the tests conducted include thermal stability test using TGA (thermogravimetric analyser), determination of glass transition temperature (Tg) using DSC (differential scanning calorimetry), plasticizer migration and leaching resistance test, morphology study of plasticized PVC films using FESEM (field emission scanning microscope), toxicity test, and tensile test. Owing to the plasticizing effect of the palm oil-based compound, Tg of the plasticized PVC has decreased to an average of 65 °C at 20wt % loading of plasticizer in PVC matrix. As for the thermal stability study, result from the analysis shows that polymeric plasticizer is able to contribute positively to the thermal stability of the PVC. The increase in thermal stability is apparent in higher molecular weight plasticizer. Besides, thermal stability of the plastic is studied using the Kissinger’s and Flynn–Wall–Ozawa’s approaches, it shows that PVC blended with high molecular weight palm oil-based plasticizer is more thermally stable, evidenced by the increase in the activation energy of decomposition, Ed. The polymeric plasticizer is also able to contribute positively to mechanical properties of the PVC films. From the leaching resistance test, plasticizers with higher molecular weight tend to leach at lower rate compared to those with lower molecular weight. Toxicity test using brine shrimp egg shows encouraging results, where the oil-based plasticizer is considerably less toxic compared to some others of the commercial plasticizers.